Integrate then differentiate?

Calculus Level 4

Given that a a is a variable independent of the variable x , x, we define I I as follows:

I = 0 π / 2 ln ( 1 + a sin x 1 a sin x ) d x sin x . \large I = \int_0^{\pi /2} \ln \left( \dfrac{1+a \sin x}{1 - a \sin x} \right) \dfrac {dx}{\sin x}.

For a < 1 |a| < 1 , find the value of d I d a \dfrac{dI}{da} in terms of a a .

π 1 a 2 \pi \sqrt { 1-{ a }^{ 2 } } 1 a 2 π \cfrac { \sqrt { 1-{ a }^{ 2 } } }{ \pi } π 1 a 2 \cfrac { \pi }{ \sqrt { 1-{ a }^{ 2 } } } π 1 a 2 -\pi \sqrt { 1-{ a }^{ 2 } }

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

James Wilson
Dec 24, 2017

d I d a = 0 π / 2 a ln 1 + a sin x 1 a sin x d x sin x = 0 π / 2 1 a sin x 1 + a sin x sin x ( sin x ) ( 1 a sin x ) 2 d x sin x = 0 π / 2 2 d x ( 1 + a sin x ) ( 1 a sin x ) = 0 π / 2 ( 1 1 + a sin x + 1 1 a sin x ) d x \frac{dI}{da}=\int_0^{\pi/2} \frac{\partial}{\partial a} \ln{\frac{1+a\sin{x}}{1-a\sin{x}}}\frac{dx}{\sin{x}}=\int_0^{\pi/2} \frac{1-a\sin{x}}{1+a\sin{x}}\frac{\sin{x}-(-\sin{x})}{(1-a\sin{x})^2}\frac{dx}{\sin{x}}=\int_0^{\pi/2} \frac{2dx}{(1+a\sin{x})(1-a\sin{x})}=\int_0^{\pi/2} \Big(\frac{1}{1+a\sin{x}}+\frac{1}{1-a\sin{x}}\Big)dx Then I perform the tangent half-angle substitution t = tan u 2 t=\tan{\frac{u}{2}} after the substitution u = π 2 x u=\frac{\pi}{2}-x . = 0 π / 2 ( 1 1 + a cos u + 1 1 a cos u ) d u = 0 1 ( 1 1 + a 1 t 2 1 + t 2 + 1 1 a 1 t 2 1 + t 2 ) 2 1 + t 2 d t = 2 0 1 ( 1 1 + a + ( 1 a ) t 2 + 1 1 a + ( 1 + a ) t 2 ) d t =\int_0^{\pi/2}\Big(\frac{1}{1+a\cos{u}}+\frac{1}{1-a\cos{u}}\Big)du=\int_0^1 \Big(\frac{1}{1+a\frac{1-t^2}{1+t^2}}+\frac{1}{1-a\frac{1-t^2}{1+t^2}}\Big)\frac{2}{1+t^2}dt=2\int_0^1\Big(\frac{1}{1+a+(1-a)t^2}+\frac{1}{1-a+(1+a)t^2}\Big)dt = 2 1 a 2 [ arctan 1 + a 1 a t + arctan 1 a 1 + a t ] 0 1 = 2 1 a 2 ( arctan 1 + a 1 a + arctan 1 a 1 + a ) = π 1 a 2 =\frac{2}{\sqrt{1-a^2}}\Big[\arctan{\sqrt{\frac{1+a}{1-a}}t}+\arctan{\sqrt{\frac{1-a}{1+a}}t}\Big]_0^1=\frac{2}{\sqrt{1-a^2}}\Big(\arctan{\sqrt{\frac{1+a}{1-a}}}+\arctan{\sqrt{\frac{1-a}{1+a}}}\Big)=\frac{\pi}{\sqrt{1-a^2}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...